2006
DOI: 10.1002/mrd.20476
|View full text |Cite
|
Sign up to set email alerts
|

TIMP‐1 as candidate gene for embryo survival in two divergent lines selected for uterine capacity in rabbits

Abstract: Selection on uterine capacity has been used in animal breeding as a way to improve the litter size. A divergent selection experiment for uterine capacity was performed in rabbits during ten generations. After the first generations of selection, large differences in number of implanted embryos were obtained between high and low lines. The major part of the differences between lines was due to embryo survival. A segregation analysis suggested the presence of a major gene affecting the reproductive traits. The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
9
0
2
Order By: Relevance
“…In addition, a complex segregation analysis performed by Argente et al (2003) found evidence of major genes with a moderate effect on UC and a large effect on embryo survival and number of implanted embryos in these rabbit lines. Moreover, Estellé et al (2006) reported a greater expression of TIMP1 in the High line. This gene is expressed in the oviduct at 62 h of gestation.…”
Section: Introductionmentioning
confidence: 92%
“…In addition, a complex segregation analysis performed by Argente et al (2003) found evidence of major genes with a moderate effect on UC and a large effect on embryo survival and number of implanted embryos in these rabbit lines. Moreover, Estellé et al (2006) reported a greater expression of TIMP1 in the High line. This gene is expressed in the oviduct at 62 h of gestation.…”
Section: Introductionmentioning
confidence: 92%
“…Les études de gènes candidats pour les caractères de reproduction sont toutes fondées sur une seule population expérimentale sélectionnée de façon divergente pour la capacité uté-rine (nombre maximal de foetus qu'une lapine peut porter lorsque le taux d'ovulation n'est pas facteur limitant) pendant 10 générations (Mocé et al, 2004). Une association entre le polymorphisme de trois gènes (OVGP1, PGR et TIMP1) et quelques caractères de reproduction, incluant l'implantation embryonnaire et la taille de portée, a été mise en évidence dans cette population expérimentale (Estellé et al, 2006 ;Peiró et al, 2008 ;Peiró et al, 2010 ;Argente et al, 2010 ;García et al, 2010).…”
Section: Caractères De Reproductionunclassified
“…A divergent selection experiment for uterine capacity has been carried out, and results suggest the presence of a major gene affecting uterine capacity and a correlated trait, which is the number of implanted embryos (Argente et al 2003). Progesterone receptor (PRG) , oviductin , and tissue inhibitor of matrix metalloproteinase-1 (TIMP1) (Estellé et al 2006) have been studied as candidate genes. SNPs within the PRG promoter and exon 11 of oviductin identified previously (Merchan et al 2005) were tested.…”
Section: Production and Fur Traitsmentioning
confidence: 99%